2021
DOI: 10.3390/covid1010005
|View full text |Cite
|
Sign up to set email alerts
|

Cope or Perish? Managing Tipping Points in Developing Coping Strategies for Emergency Response during the First Wave of the COVID-19 Outbreak in Europe

Abstract: When the first wave of the COVID-19 pandemic started to manifest itself across the globe at an unprecedented pace and magnitude, the various emergency response strategies pursued by highly affected countries in Europe raised many questions about their supposed effectiveness. To contain the outbreak, a rapid and adequate emergency response was vital to control emergent public health risks, but emergency management was challenged by large uncertainty due to many unknowns about crucial determinants of the outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Feedback from across participants highlighted the importance of providing information that was more specific to different local areas rather than generic information about the whole region. This parallels previous findings that highlight the importance of tailoring risk information for different cultures and contexts (Mascini, 1998; van der Voorn & de Jong, 2021). Participants noted that such information needs to be updated frequently to ensure that it is current, timely and indicates the likelihood of the event occurring to encourage them to act on it.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Feedback from across participants highlighted the importance of providing information that was more specific to different local areas rather than generic information about the whole region. This parallels previous findings that highlight the importance of tailoring risk information for different cultures and contexts (Mascini, 1998; van der Voorn & de Jong, 2021). Participants noted that such information needs to be updated frequently to ensure that it is current, timely and indicates the likelihood of the event occurring to encourage them to act on it.…”
Section: Resultssupporting
confidence: 89%
“…However, there are cultural differences in how risk information is communicated (Mascini, 1998). Recent research has found that Mediterranean countries with a high level of power distance and uncertainty avoidance (Italy, France, Spain) responded to new unknown situations by communicating strong rule‐based mandatory regulations (van der Voorn & de Jong, 2021). Liberal countries do this to a lower extent due to low power distance and uncertainty avoidance (The Netherlands, the UK and Sweden) but were open to trade‐offs between various interests or experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It is also beneficial to keep in mind that the regulatory systems to check people’s compliance with preventive measures were culturally affected. For example, a recent cross-cultural study analyzed the antipandemic policy strategies of eight European countries, and showed that whether a given country deployed strong rule-based regulatory systems was associated with power distance and uncertainty avoidance at the national level [ 61 ]. Likewise, future research could examine the generality of the current study by exploring how the current findings are replicated in other societies with different regulatory schemes of information governance online, values [ 62 ], social mentality [ 63 ], and ideology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study adopts a novel approach to emphasize the role of social learning ( Coe et al, 2001 ), engaging with socioeconomic aspects of the pandemic to organize and inform communities. Our hypothesis is that disasters may provide windows of opportunity to transform traditional response mechanisms and build new narratives that the enhancement of community-based knowledge networks through tools such as data dashboards will provide pathways to a stronger and more effective model of community resilience ( Sharifi et al, 2021 ; van der Voorn and de Jong, 2021 ). Our research particularly focuses on providing a socially embedded data and visualization interface for augmenting the technological capacity of communities to comprehend rapidly evolving issues and address them in a timely and efficient manner.…”
Section: Introductionmentioning
confidence: 99%